Effectiveness of Health Education Program on Nurses’ Knowledge toward Hemodialysis at Pediatric Teaching Hospitals in Baghdad City - Saeed, Mohammed; AL-Mosawi, Khatam (Iraqi National Journal of Nursing Specialties, 2020)
Objective(s): 1- Assess the effectiveness of health educational program on nurses’ knowledge toward Hemodialysis at Pediatric Teaching Hospitals. 2-To find out the relationship between nurses’ knowledge about hemodialysis and their demographic Characteristics. Methods: The study was designed in a pre-experimental pattern for the nurses’ working in the Child Welfare Teaching Hospital and the Child’s Central Teaching Hospital, and a targeted sample consisting of (30) nurses was selected. It is tested in three periods of pre-test, the first post-test, and the second post-test. Participants were tested before implementing the tutorial (tutorial lectures began from 19 to 22 January 2020 and then after a period they were tested with a preliminary post-test (on January 22, 2020) and then after a second post-test exam was conducted (on February 23, 2020). Results: The results of the study include a low level in the assessment of nurses’ knowledge before the educational program and they became high after participating in the program in the first post-test and the second post-test Recommendations: This study implement an educational program regarding nurses’ knowledge about hemodialysis center in Children Welfare Teaching Hospital and Child’s Central Teaching Hospital, in Baghdad city, and shows good improvement in nurses’ knowledge, so it’s recommended the implementation in all Iraq hemodialysis units